SURGICAL SITE INFECTIONS AMONG PATIENTS UNDERGOING ELECTIVE VERSUS EMERGENCY CAESAREAN SECTION - Kishwar, Nasreen; Hayat, Nazish; Ayoub, Saima; Ali, Sadia (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the risk factors for surgical site infection in women undergoing lower segment caesarean section and to compare the frequency of identified risk factors for surgical site infection among women undergoing elective and emergency caesarean section. Methodology: It was a cross-sectional comparative study, conducted at Hayatabad Medical Complex Peshawar from August 2014 to August 2015. Consecutive 195 post operative cases of emergency and elective caesarean section with surgical site infection were enrolled into the study. The patients were followed on the 3rd to 5th post-operative day and on 28th day thereafter. Final outcome i.e. surgical site infections (SSI) was measured on 28th day by researcher and SSI were labeled as positive, as per operational definition. Results: A total of 195 post-operative cases diagnosed with surgical site infection, were studied during the specified period. Of these 164(84.1%) were delivered with emergency caesarean section whereas 31(15.9%) by elective caesarean section. Average age of the patients was recorded 27.8 ± 7.7 (ranging from 21 to 40) years, average parity of the women was recorded 4.4±1.6 (range 0-9), average gestational age of the women was recorded 38±1.3 (ranging from 37 to 40) weeks. Average BMI of the patients was recorded 29.3±4.6 (ranging from 20 to 45). In this study BMI of more than 35kg/m2 was associated with higher rate of SSI. Conclusion: Obesity, gestational age, educational and economic status are risk factors for surgical site infections; more so following emergency vs elective caesarean sections.